2019
DOI: 10.21873/anticanres.13818
|View full text |Cite
|
Sign up to set email alerts
|

Bis(4-hydroxy-2H-chromen-2-one) Coumarin Induces Apoptosis in MCF-7 Human Breast Cancer Cells Through Aromatase Inhibition

Abstract: Aim: The present investigation aimed to examine the therapeutic potential of the new coumarin derivative bis(4-hydroxy-2H-chromen-2-one) coumarin (4HC) against breast cancer. Materials and Methods: For this purpose, the effects of 4HC treatment on the proliferation of MCF-7 breast cancer cells and on MCF-10a non-cancerous cells were evaluated using a fluorescent assay. Cell cycle distribution and apoptosis were measured by image cytometry. The expression level of aromatase (CYP19A1) and apoptosis-related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In the present study, it was observed that coumarin 2k determined cell arrest of TPC-1 cells in the G2/M phase, indicating the apoptotic mode of cell death and inhibition of DNA synthesis (S phase reduction). This finding is consistent with previous investigations reporting that coumarins able to induce cytotoxicity by inducing G2/M and S phases arrest in different cancer cell lines [46,47].…”
Section: Effect Of Coumarins 2k and 2h On The Different Phases Of The...supporting
confidence: 94%
“…In the present study, it was observed that coumarin 2k determined cell arrest of TPC-1 cells in the G2/M phase, indicating the apoptotic mode of cell death and inhibition of DNA synthesis (S phase reduction). This finding is consistent with previous investigations reporting that coumarins able to induce cytotoxicity by inducing G2/M and S phases arrest in different cancer cell lines [46,47].…”
Section: Effect Of Coumarins 2k and 2h On The Different Phases Of The...supporting
confidence: 94%
“…136) possessed marked antitumor activity against the MCF-7 cancer cell line by inducing cell cycle arrest in the G2/M phase. 209 A series of hydrazide-hydrazone and amide-substituted coumarin derivatives was synthesized and evaluated in vitro for their antitumor activity. 210 Among them, compound 140a (Fig.…”
Section: Miscellaneous Coumarin Hybridsmentioning
confidence: 99%
“…Coumarins are derivatives of 2H-1-benzopyran-2-one, which naturally occurs in plants as free coumarins or their glycoside derivatives (Kashman et al, 1992;Currens et al, 1996;McKee et al, 1998;Creagh et al, 2001;Shokoohinia et al, 2018;Bhatia and Rawal, 2019;Kawai et al, 2019;Li et al, 2019;Lin et al, 2019;Makowska et al, 2019;Ramdani et al, 2019;Selvaraj et al, 2019;Wang et al, 2019;Zhang and Xu, 2019). Coumarins have been known for their proapoptotic anticancer activity with inhibitory effects on tumor-promoting signal transduction pathways as well as antiviral activity (Kashman et al, 1992;Currens et al, 1996;McKee et al, 1998;Creagh et al, 2001;Shokoohinia et al, 2018;Bhatia and Rawal, 2019;Kawai et al, 2019;Li et al, 2019;Lin et al, 2019;Makowska et al, 2019;Ramdani et al, 2019;Selvaraj et al, 2019;Wang et al, 2019;Zhang and Xu, 2019). The naturally occurring coumarin derivatives, (+)-calanolide A and (-)-calanolide B, have been identified as inhibitors of non-nucleoside HIV-1-specific reverse-transcriptase inhibitory activity (Kashman et al, 1992;Currens et al, 1996;Creagh et al, 2001).…”
Section: Coumarins As a New Class Of Bruton's Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Several semi-synthetic calanolide derivatives have been developed as antiviral drug candidates (Creagh et al, 2001;Sagiv-Barfi et al, 2015;Chen et al, 2016). Researchers have hybridized coumarin moieties with other anticancer pharmacophores as a strategy of developing novel anticancer drugs (Flavin et al, 1996;Bhatia and Rawal, 2019;Kawai et al, 2019;Lin et al, 2019;Makowska et al, 2019;Ramdani et al, 2019;Selvaraj et al, 2019;Wang et al, 2019;Zhang and Xu, 2019). In addition, some natural coumarins such as Psoralidin (Li et al, 2019) and Osthol (Shokoohinia et al, 2018) have been reported to exhibit potent in vitro and in vivo anticancer activity.…”
Section: Coumarins As a New Class Of Bruton's Tyrosine Kinase Inhibitorsmentioning
confidence: 99%